Contributions of the University Extension in Environmental Education for the Management of Solid Waste in the UFCG - CAmpus Pomba - Nogueira Medeiros, Amanda; Gualberto de Andrade Sobrinho, Luiz; Rocha Neto, Olavio; Dantas Leite, Iris Rebeca; da Silva Medeiros, José Ludemário; Tiburtino Brasil, Jesus Carlos; da Silva, Elisângela Maria (Guará Journal, 2018)
The article reports the Extension Project carried out, through environ-mental education, that aimed to encourage a change of thought and behavior in order to promote sustainable attitudes about the problem of generation and environmentally adequate disposal of solid waste generated by students of the first graduation period Of the Federal University of Campina Grande - Campus of Pombal. The project involved 16 (sixteen) classes of incoming students from the Agronomy, Environmen-tal Engineering, Civil Engineering and Food Engineering courses of the CCTA/UFCG Pombal Campus, corresponding to 378 (three hundred and seventy-eight) students who attended the lectures on “Solid Waste Man-agement” and answered the questionnaires consisting of 20 (twenty) questions. The execution of the project, in its two years, was fundamental to bring the academic community closer to the reality of the problems involved in the issue of solid waste management.